Fertilization and irrigation regimes influence on seedling attributes and field performance of Pinus tabuliformis Carr. (28th September 2018) - Shi, Wenhui; Grossnickle, Steven C; Li, Guolei; Su, Shuchai; Liu, Yong
Abstract: Fertilization and watering are important nursery cultural practices for seedling production, though few studies have investigated the combined effects of fertilizer and watering rates on nursery attributes and field performance of container-grown pine seedlings. Four subirrigation rates ranging from 55 to 85 per cent gravimetric water content ( θ g ) and three rates of controlled-release fertilizer (CRF) from 50 to 150 mg N·seedling −1 were examined on Pinus tabuliformis in this study. Seedling attributes were assessed at the end of the nursery growing season. Field performance was monitored over four years. In the nursery, seedling shoot growth and N loading increased with CRF and subirrigation rates. Root mass, and total P and K content declined at 150 mg·N·seedling −1 rate when combined with 55 or 65 per cent θ g . After field planting, initial seedling attributes, especially root mass and plant P and/or K content, strongly affected seedling survival and growth. Maximum field survival and the largest seedlings were achieved at the combined rates of 100 mg N·seedling −1 CRF and 75 per cent θ g after four years. We concluded that optimal fertilization and irrigation rates should be considered together to produce P. tabuliformis container-grown seedlings with desirable seedling attributes for field performance.